Beyond Firearms: Mapping Global Patterns of Non-Firearm Homicide in Comparative Criminological Perspective - Zul Khaidir Kadir (Punggawa Global Research: Jurnal Multidisiplin, 2026)
This article examines global patterns of non-firearm homicide from a comparative criminological perspective. While homicide research is often dominated by firearm-centered debates, especially in regions where gun violence drives national homicide rates, lethal violence across the world is not reducible to firearms. Non-firearm homicide includes killings committed with sharp objects, blunt objects, strangulation, suffocation, bodily force, poisoning, burning, and other mechanisms that reflect different social settings, institutional conditions, and interpersonal dynamics. Using a descriptive comparative criminological design, this article maps the spatial and modal pattern of non-firearm homicide across major world regions by drawing on global homicide mechanism data and recent criminological and forensic literature. The article argues that non-firearm homicide is not a residual category after firearm homicide is removed, but represents a distinct field of lethal violence that is often linked to domestic settings, interpersonal disputes, sharp-force access, local conflict, weak guardianship, and situational escalation. The analysis shows that firearm dominance in the Americas does not represent the global structure of homicide. In Europe, Asia, and parts of Africa, non-firearm mechanisms remain central to the study of lethal violence. This article contributes to global homicide studies by developing a mapping framework that distinguishes regional homicide burden, weapon modality, situational ecology, and data limitations. It concludes that non-firearm homicide deserves systematic attention in comparative criminology because it reveals forms of lethal violence that are obscured by gun-centered criminological analysis.